TECHNOLOGIES OF FORMATION OF VISUAL-IMAGE THINKING OF PRESCHOOL CHILDREN (Conferencea, 2024)
This article explores the role of modern educational technologies in fostering the development of visual-image thinking in preschool-aged children. By analysing a range of methods and tools, the paper identifies key strategies that can enhance the cognitive and creative capacities of young learners. It also discusses the benefits of using visual aids, interactive games, and digital platforms to stimulate imagination and improve problem-solving skills. Suggestions for implementing these technologies in early childhood education are provided, along with considerations for educators seeking to integrate these approaches into their teaching practices.